A high‐safety, flame‐retardant cellulose‐based separator with encapsulation structure for lithium‐ion battery - Jinzhou Fu; Hanwei Wang; Zhichen Du; Yao Liu; Qingfeng Sun; Huiqiao Li (SmartMat, 2023)
Abstract The safety issues of lithium‐ion batteries have received attention because flammable organic electrolytes are used. Also, the commercial polyolefin separator will undergo severe thermal shrinkage when the internal temperature of the battery increases to 130–160°C, which increases the risk. Therefore, the development of a high thermal stability and high‐safety separator is an effective strategy to improve battery safety. Herein, we design a green, cellulose‐based separator (Cel@DBDPE) with a unique encapsulation structure for lithium‐ion batteries, in which functional flame retardants (DBDPE) are wrapped in microscrolls formed by the self‐rolling of 2D cellulose nanosheets upon freeze‐drying. This structure can firmly anchor DBDPE particles in the separator to prevent them from undergoing exfoliation and does not affect the properties of the separator, such as the thickness and the pore structure. Compared with commercial polypropylene, Cel@DBDPE has excellent thermal stability and flame retardancy. The former makes it less prone to thermal shrinkage and the latter can effectively prevent the combustion of the electrolyte, showing an efficient self‐extinguishing ability. Moreover, the Cel@DBDPE is only 15 μm in size and has competitive properties comparable to polypropylene. Thus, there is no sacrifice in the electrochemical performance of battery when the Cel@DBDPE is used as separator. This study provides a new structural design for the construction of a high‐safety separator.